Randomized, double-blind, placebo-controlled pilot study of metformin as an adjunctive therapy in Parkinson’s disease - AlRasheed, Hayam Ali; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Elberri, Eman I.; Kotkata, Fedaa A.; El Sabaa, Ramy M.; Elmorsi, Yasmine M.; Kamel, Mostafa M.; Negm, Walaa A.; Hamouda, Amir O.; Aldossary, Khlood Mohammad; Salahuddin, Muhammed M.; et al. (Frontiers in Pharmacology, 2025)
BackgroundParkinson’s disease (PD) is caused by the progressive loss of dopaminergic neurons in the substantia nigra. Neuroinflammation is considered a key factor contributing to the pathophysiology of PD. Current gold-standard therapies for PD provide only symptomatic relief without slowing disease progression, highlighting the need to develop new disease-modifying treatments. Metformin has been demonstrated to exert a neuroprotective role in several neurodegenerative disorders including PD.AimThis study aimed to clarify the role of metformin as adjuvant therapy in patients with PD.MethodsSixty patients with PD were divided into 2 groups (n = 30). Patients in group 1 received levodopa/carbidopa (250/25 mg) three times daily for 3 months plus placebo (Control group), while those in group 2 received levodopa/carbidopa (250/25 mg) three times daily and 500 mg metformin two times daily (Metformin group). Patients were assessed via Unified Parkinson’s Disease Rating Scale (UPDRS). The serum concentrations of toll like receptor 4 (TLR-4), α-synuclein, brain derived neurotropic factor (BDNF), and high mobility group box 1 (HMGB-1) were measured before and after treatment.Primary outcomeThe improvement in UPDRS from baseline to 3 months.Secondary outcomeChange in the level of biological markers.ResultsThe control group did not show significant difference in UPDRS when compared to their baseline value by Wilcoxon test (P > 0.05), meanwhile the metformin group showed significant difference when compared to before treatment by Wilcoxon test (P < 0.05). There were no significant differences between the two groups in UPDRS after treatment (P > 0.05) by Man Whitney test. However, the metformin group showed a significant decrease in TLR-4, HMGB-1, and α-synuclein along with a statistically significant increase in BDNF (P < 0.05) when compared to its baseline and control group. The control group did not show any significant changes in all markers when compared to their baseline.ConclusionWhile no significant differences in UPDRS scores were observed between the metformin and control groups, trends in biomarker changes suggest a potential impact of adjunctive metformin use on the underlying pathophysiology of PD. Further studies are needed to assess its effects on motor symptoms over a longer duration.Clinical Trial Registrationidentifier NCT05781711.